2018
DOI: 10.1590/0001-3765201820180319
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and prospection of diazotrophic rhizobacteria associated with sugarcane under organic management

Abstract: Microorganisms associated with organic management are essential in nutrient transformation and release for plant use. The present study aimed to isolate, identify and characterize plant growth promoting diazotrophic rhizobacteria associated with sugarcane under organic management. Rhizospheres of organic sugarcane varieties IAC 911099 and CTC4 were sampled and inoculated onto nitrogen free NFb and Burk media. The isolated microorganisms were screened in vitro concerning their ability to produce plant growth pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 88 publications
(42 reference statements)
0
7
0
1
Order By: Relevance
“…Additionally, the rhizosphere soils treated with bio-organic fertilizer were also enriched in the bacterial genera Mycolicibacterium ( 58 ), Novosphingobium ( 59 ), and Sphingobium ( 60 , 61 ), which are associated with soil nutrient transformation ( 62 ). It has been reported that the addition of beneficial Bacillus spp.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the rhizosphere soils treated with bio-organic fertilizer were also enriched in the bacterial genera Mycolicibacterium ( 58 ), Novosphingobium ( 59 ), and Sphingobium ( 60 , 61 ), which are associated with soil nutrient transformation ( 62 ). It has been reported that the addition of beneficial Bacillus spp.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies also reported Pseudomonas and Bacillus as the dominant genera isolated from organic farming (Xia et al, 2015;Armalyte et al, 2019). Rodrigues et al (2018) reported Burkholderia, Bacillus and Rhizobium as the most dominant genera of diazotrophic bacterial isolated from organically grown sugarcane crops. Xia et al (2015) also managed to identify Stenotrophomonas sp., Micrococcus sp., Denococcus sp.…”
Section: Culturable Bacteria Associated With Nature Farming Systems and Their Pgp Characteristicsmentioning
confidence: 87%
“…Diversas bactérias da rizosfera já foram identificadas com efeitos antagônicos a fungos e nematoides (STURZ; NOWAK, 2000;TIAN;YANG;ZHANG, 2007;MACHADO et al, 2012), produzindo antibióticos, toxinas e enzimas, interferindo no processo de reconhecimento planta-hospedeiro, induzindo resistência ou proporcionando o desenvolvimento da planta (SIDDIQUI; SHAUKAT, 2002;BAGHEL;AKHTAR, 2007;STIRLING, 2017). Algumas das espécies mais frequentemente citadas são de Bacillus, e pelo menos parte destas forma endósporos e apresenta uma multiplicidade de mecanismos antagônicos (DOMENECH et al, 2006; GROVER; NAIN; SAXENA, 2009; KAKAR et al, 2018; ALOO; O potencial para FBN, isoladamente ou associado a outros mecanismos, foi identificado e quantificado em diferentes espécies vegetais como Dodoneae viscosa L. (AFZAL et al, 2017), milho (CARVALHO et al, 2017;GARCIA et al, 2017;MARAG;SUMAN, 2018;IKEDA et al, 2020), arroz (CHAUDHARY et al, 2012BANIK;MUKHOPADHAYA;DANGAR, 2016;BEUTLER et al, 2016;MAHMUD et al, 2020) e cana- de-açúcar (TAULÉ et al, 2012;RODRIGUES et al, 2018;MAHMUD et al, 2020).…”
Section: Mecanismos De Promoção De Crescimentounclassified